Pengaruh Kompetensi, Iklim Organisasi dan Semangat Kerja Terhadap Kepuasan Kerja Karyawan Pada PT. Perkebunan Nusantara IV Regional I Kebun Sei Silau Kabupaten Asahan - Putri Widya Ananda; Normansyah Normansyah (Ali Institute of Research and Publication, 2026)
This study aims to analyze the influence of competence, organizational climate, and work spirit on employee job satisfaction at PT. Perkebunan Nusantara IV Regional I Kebun Sei Silau, Asahan Regency. This study uses a quantitative approach with a survey method by distributing questionnaires to 84 respondents selected from the employee population. Data were analyzed using multiple linear regression to determine the influence of each variable on job satisfaction. The results show that competence, organizational climate, and work spirit have a positive and significant effect on employee job satisfaction, both partially and simultaneously. This finding indicates that job satisfaction is not only influenced by the technical aspects of the job, but also by the organizational atmosphere and the psychological drive of employees in working. From an Islamic economic perspective, job satisfaction can be understood as part of an effort to realize work that has religious values through trustworthiness, ihsan, responsibility, justice, and a productive work spirit. The implications of this study indicate that companies need to improve employee competence, build a fair and harmonious organizational climate, and foster work spirit in accordance with Islamic values so that job satisfaction can increase sustainably. The contribution of this study lies in strengthening human resource management studies by incorporating Islamic values as an ethical foundation in understanding employee job satisfaction.